Kompetensi Digital Leadership Terhadap Adopsi Teknologi Digital di Badan Penangulangan Bencana Daerah Aceh Barat - Maula, Suriyatul Maula; Munawarah, Munawarah; Aripin, Nurasma (Program Studi Ilmu Administrasi Negara Bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Digitalization in government is a crucial step to improve the efficiency, effectiveness, and quality of public services. public services. National coordinating agency for disaster management, Aceh Barat, as an institution that plays an important role in mitigating and overcoming disasters, needs to adopt digital technologies and disaster management, in adopting digital technology requires digital leadership competencies by leaders in the agency in order to optimize its performance to optimize its performance. This study aims to examine the digital leadership competencies of national coordinating agency for disaster management leaders in directing the adoption of adoption of digital technology to support rapid response and disaster mitigation in the Aceh Barat regio. This study uses a qualitative approach through in-depth interviews with key informants who were determined based on purpose sampling, namely the knowledge of knowledge of the informants with the object of research. This research identified necessary digital skills, such as digital literacy, digital vision, communication, and adaptability to technology by leaders. The focus of of this research on the National coordinating agency for disaster management, Aceh Barat, specifically examining the The Coordinator of the Disaster Management Operations Control Center, as the head of the technical field that technically interacts a lot with technology related to disaster management in West Aceh. There are four digital technology adoptions in National coordinating agency for disaster management, namely Early Warning Sensorsirene, Seismometer, Social Media Accounts, and SIMAMPU, which require competence. Social Media Accounts, SIMAMPU which require digital leadership competencies of the leaders or heads of fields who adopt them. or the head of the field that adopts it